Hugh Downman, MD (1740–1809) of Exeter and his poem on infant care. Issue 3 (1st May 2003) - Dunn, P M
Abstract : Hugh Downman is best remembered for his poem on the care of infants in which he stressed the importance of breast feeding and proper examination.